Balloon occlusion of the aorta during cardiac arrest -a death blow to the intestines? - Bjørn Hoftun Farbu; Jostein Brede (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background The use of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) in non-traumatic cardiac arrest may result in worsened intestinal ischaemia. What are the consequences? Main text Human data on REBOA in non-traumatic cardiac arrest is limited. In general, cardiac output is reduced during resuscitation, and mesenteric blood flow may be further reduced by intravenous adrenaline (epinephrine). Balloon occlusion of the thoracic aorta will potentially lead to a complete cessation of intestinal blood flow. Experimental studies demonstrate that intestinal damage increases with REBOA inflation time, and that 45–60 min of ischaemia may result in irreversible damage. However, it is unclear when intestinal ischaemia starts to affect patient-oriented outcomes. A barrier for assessing the consequences of intestinal ischemia is that it is a challenge to diagnose. A biomarker for intestinal injury, Intestinal Fatty Acid Binding Protein (IFABP), was elevated in all cardiac arrest patients and had a striking association with mortality in one study. In another study, all patients with intestinal ischemia diagnosed on CT died. However, intestinal ischemia could be a marker of whole-body ischemia and not an independent contributor to poor outcome. The clinical importance of worsened intestinal ischemia by REBOA during cardiac arrest is not established. Conclusion The impact of intestinal ischaemia following cardiac arrest is uncertain, but ischaemia is likely to be exacerbated by REBOA. However, inflation of the balloon will occur when the patient is still in cardiac arrest and is a means to achieve ROSC. Hence, we argue that the added intestinal ischaemia caused by REBOA may be of limited clinical importance, but this is still to be answered.